Pengembangan Lembar Kerja Peserta Didik (LKPD) Matematika Integrasi Nilai-Nilai Islam Pada Tingkat SMP - Azizatul Hikmah; Aisyah Nur Ilmi; Miftahul Jannah; Tri Lestari; Zakia Zahra; M. Imamuddin (Universitas Pahlawan Tuanku Tambusai, 2023)
The purpose of this research is to find the integration of Islamic values in mathematics learning in Islamic-based MTs/MPs. The Islamic values that are integrated include Islamic character values. The collection method uses literature review. Data collection techniques are carried out by collecting journals and reviewing related to the development of Learner Worksheets (LKPD) of mathematics subjects integrating Islamic values at the junior high school level, meaning that the research moves between one journal to another where each action is a step towards refining information. The results of this study found the integration of Islamic values in mathematics learning both at the level of devices and implementation of learning. In the implementation of learning, Islamic values are integrated in the material, through Islamization of mathematics (reconstructing mathematics from the context of Islamic values), Islamic mathematization (using mathematics to build awareness of Islamic values) and interconnection (functional relationship between mathematics and Islamic values). Keywords: Learning, Mathematical learning, Islamic values, Learning resources, LKPD